Autoimmune Encephalitis in the Philippines: A Scoping Review on the Treatment Gaps, Challenges, and Current State of Care - Pagaling, Gerald T.; Turalde, Christian Wilson R.; Jamora, Roland Dominic G. (Frontiers in Neurology, 2022)
Objectives We reviewed the current health service delivery for individuals with Autoimmune Encephalitis (AE) in the Philippines and to identify the gaps and challenges in its management. Methodology We conducted a scoping review of pertinent literature AE in the Philippines using the Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA) guidelines. We extracted data on epidemiology, legislation, health financing, information systems, pharmacotherapy, and healthcare services related to the management of AE in the local setting. Discussion The epidemiology of AE is still unknown. Out-of-pocket expenses contribute to most of the healthcare expenditure despite government-led programs to reduce the financial burden. The access to diagnostic examinations such as magnetic resonance imaging, electroencephalogram, and antibody testing is limited by the geographic distribution of the facilities and costs. The acute and long-term management of AE are cost-prohibitive and are not readily available. There are significant treatment gaps in the care of individuals with AE in the Philippines in terms of disease recognition, resource allocation, access to satisfactory diagnostic evaluation, and provision of prognosis-changing therapeutics. We proposed core strategies that can address these treatment gaps such as increasing awareness, improving access to health resources, adequate healthcare financing, and availability of support systems.